Efeito inibitório do óleo essencial de Thymus vulgaris L. frente a bactérias patogênicas e ácido láticas de importância em queijo de coalho - Carvalho, Rayssa Julliane de (2015)
Coalho cheese is obtained by enzymatic coagulation by the action of renin or specific enzymes, as well as using starter lactic acid bacteria (LAB) cultures that positively contribute to organoleptic aspects of the product. Some physicochemical characteristics of this cheese, as high moisture and pH, favor the growth of pathogenic bacteria frequently associated to outbreaks, such as Staphylococcus aureus and Listeria monocytogenes. The development of these pathogens in coalho cheese could be avoided by the adding of synthetic additives, however the growing interest of consumers for natural foods, free or containing low levels of chemical additives, have led the research of natural compounds with antimicrobial properties that can be used in food industry. The essential oil from Thymus vulgaris L. (TVEO), popularly known as thyme, possesses recognized antimicrobial activity against pathogenic bacteria, however there is no information about its effect on bacteria of technological interest, such as starter lactic acid cultures, used cheese manufacture. Considering these aspects, this study was performed to evaluate the inhibitory effect of TVEO on Lactococcus strains commonly used in coalho cheese processing as well as on pathogenic strains S. aureus and L. monocytogenes. For this, the values of minimum inhibitory concentration (MIC) of TVEO were determined against the test strains and the effects of TVEO on bacterial cell viability were assessed in cheese-based broth and in cheese samples. The main constituents of TVEO identified by CG-MS, were thymol (43.19%) and p-cymene (28.55%). The MIC value MIC of TVEO was 2.5 μL/mL against S. aureus and L. monocytogenes, and 1.25 μL/mL against L. lactis subsp. lactis and L. lactis subsp. cremoris in co-culture. In the assays in cheese-based broth containing TVEO at 1.25 μL/mL after 24 h, a decrease of approximately 1 log CFU/mL in the viable cell counts of L. monocytogenes and Lactococcus spp. was observed. At the same concentration, the TVEO presented no inhibitory effects on the growth of S. aureus. Only when TVEO was incorporated in growth media at 5 μL/mL viable cell counts of S. aureus and L. monocytogenes presented a sharp decrease over time, showing kill-time curves shape similar to that obtained when starter co-culture was exposed to TVEO at 2.5 μL/mL. TVEO at 5 μL/mL decrease 2 log CFU/mL the viable cell counts of the starter co-culture after 12 h of exposure. In the assays with coalho cheese added of TVEO at 1.25 μL/g no reduction in viable cells counts of co-culture or pathogenic bacteria was observed. However, OETV at 2.5 μL/g caused a decrease in viable cell counts of all tested bacteria tested after 72 h of exposure, varying from 0.3 to 1.0 log CFU/g. The results suggest that TVEO concentrations required to control pathogenic bacteria in coalho cheese should be carefully considered, since they can have negative effects on the growth and survival of lactic bacteria of the lactic fermentum.